Let's solve each equation step by step.
(a) \( 4 - \text{blank} = 4 + 1 \)
First, simplify the right-hand side: \[ 4 + 1 = 5 \]
Now, the equation is: \[ 4 - \text{blank} = 5 \]
To isolate "blank," subtract 4 from both sides: \[ -\text{blank} = 5 - 4 \] \[ -\text{blank} = 1 \]
Now, multiply both sides by -1: \[ \text{blank} = -1 \]
So the answer for (a) is \( \text{-1} \).
(b) \( 1 - 8 + 1 + \text{blank} \)
First, simplify the left-hand side: \[ 1 - 8 = -7 \] Now add 1: \[ -7 + 1 = -6 \]
Now the equation is: \[ -6 + \text{blank} = 0 \]
To isolate "blank," add 6 to both sides: \[ \text{blank} = 0 + 6 \] \[ \text{blank} = 6 \]
So the answer for (b) is \( \text{6} \).
Final Answers:
(a) -1
(b) 6